2006
DOI: 10.1002/jso.20694
|View full text |Cite
|
Sign up to set email alerts
|

Seminars: Local and regional anesthesia for thyroid surgery

Abstract: Local and regional anesthesia is safe and well tolerated for the majority of thyroid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 17 publications
2
31
0
1
Order By: Relevance
“…To decrease the postoperative pain and reduce the need for analgesics following thyroidectomy surgery, preoperative oral controlled-release analgesia with opioids and alternative regional techniques such as incisional local anesthesia, intraoperative bilateral superficial and/or deep cervical plexus block, local wound infiltration with local analgesia have also been suggested recently (20,21,23,(27)(28)(29). Performing thyroidectomy under local or regional anesthesia rather than general anesthesia has also been suggested to control postoperative pain (30).…”
Section: Discussionmentioning
confidence: 99%
“…To decrease the postoperative pain and reduce the need for analgesics following thyroidectomy surgery, preoperative oral controlled-release analgesia with opioids and alternative regional techniques such as incisional local anesthesia, intraoperative bilateral superficial and/or deep cervical plexus block, local wound infiltration with local analgesia have also been suggested recently (20,21,23,(27)(28)(29). Performing thyroidectomy under local or regional anesthesia rather than general anesthesia has also been suggested to control postoperative pain (30).…”
Section: Discussionmentioning
confidence: 99%
“…When methods applied by adding bilateral deep cervical plexus block to BSCPB without general anaesthesia were examined, it was observed that patients are discharged from hospital much earlier with this method, however patients should be selected very carefully in terms of surgical procedures, general conditions of patients and anxiety, otherwise both patient and surgeon comfort grow worse (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, local anesthesia without cervical plexus block is limited to central thyroid resections, for example isthmusectomy. Although more extensive thyroid resections can be performed under strict local anesthesia, adjuvant cervical plexus blocks facilitate deeper dissection and reduce the need for repeated injections of local anesthetic during the operation [15].…”
Section: Local Anesthesia and Cervical Plexus Blockmentioning
confidence: 99%
“…Alone or in combination, lidocaine and bupivacaine are excellent choices; such combinations of short and longer-acting anesthetic agents can be supplemented with epinephrine (1:100,000 or 1:200,000) to prolong the duration of the anesthetic [13,15,17]. The cervical nerve block may be executed by the anesthesiologist or surgeon before the patient enters the operating room, or by the surgeon just before making the incision.…”
Section: Local Anesthesia and Cervical Plexus Blockmentioning
confidence: 99%